Warming Up to Oxazole: Noncryogenic Oxazole Metalation and Negishi Coupling Development - Geier, Michael J.; Wang, Xiaotian; Humphreys, Luke D.; Calimsiz, Selcuk; Scott, Mark E. (Synlett, 2019)
This report details the development of several suitable noncryogenic metalation conditions for the synthesis of oxazole zincate. Subsequent rounds of high-throughput catalyst screening ultimately led to the identification of several suitable Pd sources that can be used for the Negishi coupling of unsubstituted oxazole. The scope and generality for one of the reported conditions is also presented.
Keywords: Negishi coupling; catalysis; cross-coupling; organozinc; oxazole; high-throughput screening